Linked Economic and Animal Systems (LEAS) Model: Technical documentation - Aragie, Emerta A.; Beyene, Seneshaw Tamiru; Legesse, Ermias; Thurlow, James (International Food Policy Research Institute, 2021)
The herd dynamics model (HDM) component of the Linked Economic and Animal Systems (LEAS) model specifically documented here is developed in the context of the Feed the Future Innovation Lab for Livestock Systems financed by the United States Agency for International Development (USAID) and managed by the University of Florida’s Institute of Food and Animal Sciences. The main objective of this project is to develop a comprehensive analytical approach or systems model capable of assessing (i) how animal herd or flock sizes change over time and in response to on-farm policies; (ii) how alternative national trends and policies affect future development of the livestock system as a whole; (iii) how changes in livestock policies affect people working throughout the livestock system; and (iv) how changes in animal-source food (ASF) production and prices affect the real incomes and consumption patterns of different population groups. The HDM developed provides a highly detailed description of the cattle sector while laying a framework that can be easily adapted to other types of livestock. The model allows one to closely examine the performance of the livestock sector disaggregated by agroecology zones or regions. The HDM is linked both ways with a core economywide model through economic variables such as relative prices of livestock activities, prices and availability of intermediate inputs including feed, and changes in supply of livestock capital in the meat and milk production sectors. Given the complex interplay in the livestock sector such as offtake decisions, death rates, milk and meat yield, and feeding practices (through quality indexed feed demand), the HDM developed under this project is a fully dynamic livestock sector model that provides several avenues for analysis on livestock management, the sector’s future trajectory, and its dynamics, given risks and opportunities within the sector and beyond.